2007
DOI: 10.1088/0957-4484/18/31/315604
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of PbF2nanorods in a microemulsion system

Abstract: Single-crystalline PbF 2 nanorods with a diameter of 100-500 nm and length of 1-10 μm have been successfully synthesized by a simple sonochemical route in a microemulsion system at room temperature. The morphologies and structures of the nanorods were characterized by x-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, and high-resolution transmission electron microscopy. The experimental results showed that polyethylene glycol 6000 played an important role in the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Sample 1 # with F/Pb ratio of 2.5 showed a pure α-PbF 2 crystalline structure (according to JCPDS card no. 06-0288), similar results could be found in references [5][6][7][8]. When the F/Pb ratio was increased to 5 (Figs.…”
Section: Xrd and Sem Results Of The Hydrothermal Synthesized Pbf 2 Posupporting
confidence: 87%
See 3 more Smart Citations
“…Sample 1 # with F/Pb ratio of 2.5 showed a pure α-PbF 2 crystalline structure (according to JCPDS card no. 06-0288), similar results could be found in references [5][6][7][8]. When the F/Pb ratio was increased to 5 (Figs.…”
Section: Xrd and Sem Results Of The Hydrothermal Synthesized Pbf 2 Posupporting
confidence: 87%
“…Xu et al successfully synthesized octahedral and wheat like α-PbF 2 microcrystal by a sonicationmicroemulsion method. When polyethylene glycol 6000 (PEG-6000) was added, perfect nanorod like α-PbF 2 was obtained [8].…”
Section: Size and Morphology Of The Orthorhombic Pbf 2 Microcrystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al demonstrated that α-PbF 2 nanorods can be prepared via a sonochemical route in microemulsion system and the structure exhibits strong green emission. 7 More recently, Xu has showed that octahedral PbF 2 can be produced by the sonochemical method based on oriented attachment process. 8 More recently, Zhu et al have demonstrated that β-PbF2 microsphere and α-PbF 2 microrods with different size can be controllably fabricated by hydrothermal methods.…”
Section: Introductionmentioning
confidence: 99%